THE REVEAL OF ARTIFICIAL INTELLIGENCE IN INFORMATION SOCIETY (Conferencea, 2021)
This article discusses the importance of Artificial Intelligence tools in the process of human intelligence. The issue of human thinking and intelligence is an important element of direct knowledge. Intelligence differs from thinking by its specific content. Intelligence refers to an entire system of individual cognitive abilities such as intuition, perception, memory, imagination, thinking, imagination and focus. Artificial Intelligence is a technical opportunity for scientific and practical work, the main task of which is to discover new aspects of human activity in different directions. In short, if the notion of intellect is the main source of human knowledge, artificial intelligence must act as its helper. If people make the most of their intellectual potential, it will surely provide them with a brighter future